Effect of golden apple snail, trash fish and combination of golden apple snail and trash fish on the growth and survival of african catfish fingerling Clarias gariepinus (Burchell, 1822). - Mabunay, Sandra R. (1997.)
The African catfish, Clarias gariepinus is synonymous with Clarias lazera, Calrias sengalensis and Clarias mossambicus. It is favored by aquaculturists because of its ability to withstand adverse conditions such as low dissolved oxygen level and high stocking rates., Growth is the most important criterion for measuring response to experimental diets. And the most important element, for carnivorous fish, is protein. However, amino acid composition of the protein affects feed intake, therefore it would also affect growth rate. This study aims to determine the effects of golden apple snail, trash fish and combination of golden snail and trash fish on the growth and survival of African catfish fingerling, and to compare the efficiency of these feeds and feed combination in the culture of Clarias gariepinus. Fingerlings with initial weight and length of 2.13 {ogon} 0.08 (g) and 6.54 {ogon} 0.08 (cm), respectively were used as culture animals. The experiment consisted of four treatments: Treatment A-commercial feed, Treatment B-trash fish, Treatment C-golden apple snail, and Treatment D-combination of trash fish and golden apple snail. Treatments were arranged in a completely randomized design. The amount of feed given per day was 5 of the fish' body weight. Fish weight and length gain were measured every after 10 days. Survival, dissolved oxygen, pH and temperature were monitored daily. The result of the study showed that fingerlings fed with commercial feed consistently got the highest growth rate, specific growth rate, lowest feed conversion ratio and highest survival rate as compared to the 3 other diets. Comparing the three experimental treatments, fingerlings fed with golden apple snail gave a higher specific growth rate and lower feed conversion as compared to fingerlings fed with trash fish and combination diet. Fingerlings fed with trash fish gave negative growth rate as indicated by weight loss. Commercial feed, therefore, is still considered the best feed in the culture of Clarias gariepinus. Golden apple snail, trash fish and combination of trash fish and golden apple snail cannot be used as an alternative feed for commercial diet because their utilization resulted to low specific growth rate and high feed conversion ratio as compared to commercial feed.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Golden Apple Snail; Trash Fish; Fingerlings -- African Catfish; Clarias gariepinus